2020
DOI: 10.3390/toxins12120797
|View full text |Cite
|
Sign up to set email alerts
|

Does Botulinum Toxin Treatment Affect the Ultrasonographic Characteristics of Post-Stroke Spastic Equinus? A Retrospective Pilot Study

Abstract: Equinovarus/equinus foot is a pattern most commonly treated with botulinum toxin type A in patients with post-stroke spasticity involving the lower limbs; the gastrocnemius is the muscle most frequently injected. Spastic equinovarus/equinus can present a mixture of conditions, including spasticity, muscle/tendon shortening, muscle weakness and imbalance. In this study, we wanted to determine whether botulinum toxin treatment affects the ultrasonographic characteristics of post-stroke spastic equinus. The same … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 16 publications
0
9
0
Order By: Relevance
“…In 2020, Picelli et al investigated the clinical and US architectural changes induced by BoNT-A in 21 post-stroke patients with spastic equinus. 36 At four weeks post-injection, they did not observe any significant effect of BoNT-A treatment on ultrasonographic characteristics (EI, muscle thickness, and pennation angle).…”
Section: Resultsmentioning
confidence: 82%
See 3 more Smart Citations
“…In 2020, Picelli et al investigated the clinical and US architectural changes induced by BoNT-A in 21 post-stroke patients with spastic equinus. 36 At four weeks post-injection, they did not observe any significant effect of BoNT-A treatment on ultrasonographic characteristics (EI, muscle thickness, and pennation angle).…”
Section: Resultsmentioning
confidence: 82%
“…The US has become a popular tool that has risen to fulfill the need for a more reliable and accessible method to assess spastic muscle and its evolution over time ( Table 3 ). 12 Three main US modalities have been used to study spastic muscles: morphological changes, 36-52 sonoelastography,36,38,43,45,47,51,53-65 and echogenicity.36,37,44,49,52,66-71…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Ultrasonographic characteristics (i.e., muscle echo intensity, muscle thickness, posterior pennation angle, Achilles tendon thickness, and sonoelastography) have been used to evaluate effect of BoNT-A treatment with post-stroke spasticity [ 23 , 32 , 33 ]. Picelli et al evaluated Achilles tendon stiffness by sonoelastography before and after BoNT-A treatment at approximately 1 month interval, but found no significant changes [ 33 ]. Previous studies in post-stroke patients have reported a significant reduction of SWV in Biceps brachii of patients with post-stroke upper limb spasticity after BoNT-A injection [ 25 , 31 ].…”
Section: Introductionmentioning
confidence: 99%